Migration and Integration in Europe, Southeast Asia, and Australia A Comparative Perspective - Pietsch, Juliet; Clark, Marshall (Global Asia, 2015)
This volume brings together a group of scholars from a wide range of disciplines to address crucial questions of migration flows and integration in Europe, Southeast Asia, and Australia. Comparative analysis of the three regions and their differing approaches and outcomes yields important insights for each region, as well as provokes new questions and suggests future avenues of study.